Rancangan Kesinambungan Perniagaan (BCP) oleh Angsana Mall : Kemampanan Semasa Pandemik - Hazizah Zulkarnaini,; Md Ariffin, Khadijah; Latifah Md Ariffin,; Mohd Safiee Idris, (Research in Management of Technology and Business, 2022)
A Business Continuity Plan (BCP) is important to ensure the continuity of a business operation. This plan helps organizations prepare for disasters or pandemics Covid-19 and allows business to run as usual after a disaster has occurred to the organization. Effective BCP implementation starts from employee awareness of the activities involved in BCP. This study aims to identify the effect of the Movement Control Order (MCO) on Angsana Mall in Johor Bahru and examine the effective strategies that have been carried out by the manager of the mall in managing the building by using BCP during the MCO. The method used is a qualitative method, which is a semi-structured interview session with respondents from the center management responsible for providing BCP at the Angsana Mall shopping center. The result of this study is that there are seven (7) main parts in this study interview regarding the effect of the MCO on Angsana Mall and also the strategies that have been carried out by the management in terms of security, critical maintenance of the building system, information technology, cleaning services, communication , finance, and marketing. The analysis results of this study can be used as a reference source to reduce the operational risk of shopping centers in the future.